Stem cells for age-related macular degeneration - L.K. Moshetova; O.I. Abramova; I.N. Saburina; K.I. Turkina (РМЖ "Клиническая офтальмология")
L.K. Moshetova1, O.I. Abramova1, I.N. Saburina2,3, K.I. Turkina2 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2Institute for Molecular and Personalized Medicine, branch of Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 3Institute of General Pathology and Pathophysiology, Moscow, Russian Federation Unique biological properties of stem cells offer infinite opportunities to use them for numerous degenerative disorders. Thus, in ophthalmology cell replacement therapy is a prospective approach to manage irreversible retinal cell death in age-related macular degeneration. Currently, this disorder is the leading cause of disability, blindness, and reduced quality of life in people aged over 50 in developed countries and is therefore important medical social issue. None of current treatment approaches can either turn back or prevent pre-existing retinal cell degeneration. Therefore, cell replacement therapy and regenerative medicine are promising modalities since they are characterized by much greater prospects than traditional treatment. This paper reviews recent advantages in the treatment for this incurable disorder using various types of stem cells (i.e., mesenchymal, embryonic, and induced pluripotent stem cells). This paper first gives a brief overview of age-related macu lar degeneration and then describes the methods of retinal cell generation. Keywords: age-related macular degeneration, stem cells, eye tissue regeneration, pluripotent stem cells, clinical application of stem cells, regenerative medicine, cell therapy, tissue engineering. For citation: Moshetova L.K., Abramova O.I., Saburina I.N., Turkina K.I. Stem cells for age-related macular degeneration. Russian Journal of Clinical Ophthalmology. 2019;19(3):143–148. About the authors: 1Larisa K. Moshetova — MD, PhD, Academician of RAS, Head of the Department of Ophthalmology, ORCID iD: 0000-0002-5899-2714; 1Olga I. Abramova — MD, postgraduate student of the Department of Ophthalmology, ORCID iD 0000-0002-6156-6126; 2,3Irina N. Saburina — PhD, Professor, Principal Researcher, Head of Laboratory, ORCID iD 0000-0003-2014-2535; 1Kseniya I. Turkina — MD, PhD, associate professor of the Department of Ophthalmology, ORCID iD 0000-0002-4989-7467. 1Russian Medical Academy of Continuous Professional Education. 2/1, Barrikadnaya Str., Moscow, 125993, Russian Federation. 2Institute for Molecular and Personalized Medicine. 7, Build. 2, 2nd Botkinskiy Pass., Moscow, 125284, Russian Federation. 3Institute of General Pathology and Pathophysiology.  8, Baltijskaya Str., Moscow, 125315, Russian Federation. Contact information: Olga I. Abramova, e-mail: abramovao2019@mail.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 17.07.2019.